2021
DOI: 10.1002/jper.20-0394
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal and caries status in unexplained female infertility: A case–control study

Abstract: Background: The aim of this study was to investigate the possible association between maternal periodontal disease and dental caries that affect oral health and unexplained infertility. Methods: This cross-sectional case-control study included 50 fertile women and 50 women with unexplained infertility aged 21 to 39 years. Dental and periodontal parameters were examined to evaluate the oral health of the participants. According to the new periodontal disease classification, periodontitis severity was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
8
1
Order By: Relevance
“…Thus we can explain a smaller number of positive tests. This is inconsistent with published studies that have shown poorer periodontal status in patients with idiopathic infertility ( 1 , 8 , 10 , 12 ). A possible explanation might be that infertile women included in our study were more aware of their oral health, or that they had different economic or educational background which might also affect their oral health, which was not considered in this study.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Thus we can explain a smaller number of positive tests. This is inconsistent with published studies that have shown poorer periodontal status in patients with idiopathic infertility ( 1 , 8 , 10 , 12 ). A possible explanation might be that infertile women included in our study were more aware of their oral health, or that they had different economic or educational background which might also affect their oral health, which was not considered in this study.…”
Section: Discussioncontrasting
confidence: 90%
“…Some authors have shown worse periodontal status in infertile patients and suspected that this is a factor that complicates conception ( 1 , 6 - 10 , 12 ). On the contrary, others have reported that the periodontal status of patients has not affected the outcome of the IVF procedure ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…All included studies were published between 1994 and 2022. The characteristics of these 18 studies were shown in Table 1 , including 10 studies [ 26 35 ] in relative to the prevalence of caries in patients with periodontitis, 5 [ 29 32 , 36 ] containing the prevalence of periodontitis in patients with caries and 7 studies [ 33 , 37 42 ] covering the association between pathogenic bacteria related to two diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, beyond its impact on periodontal tissues, periodontitis also has implications for other bodily systems. Some observational studies have shown that periodontitis may pose potential risks for female reproductive difficulties and adverse pregnancy outcomes, such as female infertility [ 4 ], endometriosis [ 5 ], spontaneous miscarriages occurring before 20 weeks of gestation [ 6 ], and the delivery of low-weight babies, defined as those weighing less than 2.5 kg at birth [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%